PATIENT'S DISCOMFORT ASSOCIATED WITH FIXED ORTHODONTIC APPLIANCES TREATMENT - Indah Yuri Noviaranny; Nuramira Hafiza bt Abd Halim; Aimi Juani binti Ahmad Zuhri (Journal of Health and Dental Sciences, 2023)
To determine the prevalence and factors causing discomfort during fixed orthodontic treatment. Two hundred patients of fixed orthodontic patients in UiTM clinics who were willing to participate and could consent to the research were selected. The participants were randomly selected for this research in the odd number sequence from the population size of 740 individuals. Data was collected employing an Oral Impact on Daily Performance questionnaire to assess discomfort intensity and bio-psychosocial variables. Statistical analysis used was descriptive statistics and chi-squared statistics. The prevalence of discomfort in patients with fixed orthodontic appliances was 92% (mean: 0.92, standard deviation: 0.27), which covers 184 of the samples. Eating food (68%), speaking clearly (37%), cleaning teeth (64%), sleeping (21%), smiling and laughing, and showing teeth without embarrassment (21%) remained independently associated with a greater prevalence of discomfort (P ≤ 0.05). The patient wearing fixed orthodontics appliances has a high prevalence of discomfort. The factors associated with the discomfort included eating food, speaking, cleaning teeth, sleeping, and smiling and laughing, showing teeth without embarrassment. DOI : 10.54052/jhds.v3n1.p31-42